MMDES: Multimedia Digital Ecosystem - Asres Kidanu, Salomon (2016)
19th IEEE International Conference on Computational Science and Engineering (CSE 2016), is the event, in a series of highly successful International Conferences on Computational Science and Engineering, held mainly as the International Workshop on High Performance Scientific and Engineering Computing for 11 editions. August 24-26, 2016 - Paris, France